HIV status and hearing loss among children between 6 and 12 years of age at a large urban health facility in south western Uganda. (October 2017) - Nakku, Doreen; Nyaiteera, Victoria; Llowet, Evelyn; Nanseera, Dennis; Nakalema, Gladys; Westerberg, Brian; Bajunirwe, Francis
Abstract: Introduction: Pediatric HIV infection and treatment may increase the risk for hearing loss (HL), both sensorineural (SNHL) and conductive hearing loss (CHL). There is limited data on this subject, especially from sub Saharan Africa. The aim of this study was therefore to compare the prevalence of hearing loss among HIV positive and negative children, to determine the types of hearing loss and whether Nevirapine (NVP) based antiretroviral therapy (ART) is associated with HL. Methods: We conducted a cross sectional study at two tertiary health facilities in south western Uganda. We consecutively enrolled 79 HIV negative and 148 HIV positive children aged between 6 and 12 years. Inclusion criteria were completion of written consent, ability to follow instructions to perform an audiogram and absence of congenital HL. We conducted hearing screening using the iPad Shoebox ® audiometer, and confirmatory assessments were conducted using pure tone audiometry. Hearing was classified as either normal hearing, CHL, SNHL or mixed. Results: Of the 227 children enrolled, 115 (50.7%) were female. The mean age was 9.2 years (median = 9). Based on self-report, frequency of HL among HIV positive children was 6.8% and 20.3% among HIV negative children (p=<0.01). Using objective measures, prevalence of HL among the HIV positive children was 8.8% compared to 10.1% among the HIV negative children (p = 0.74). CHL was generally more frequent than SNHL but SNHL occurred more frequently among HIV positive (7.4%) compared to HIV negative children (3.8%). No association was found between NVP based ART and HL (p = 0.41). Logistic regression showed that older age of the child (p = 0.01), previous ear infection (p=<0.01), tuberculosis (TB) treatment (p=<0.01) and long term duration on ART (p=<0.01) were significantly associated with HL. Age (p = 0.02), previous ear infection (p = 0.01) and TB treatment (p = 0.005) remained significant in the multiple regression model. Conclusion: Prevalence of HL is similar among HIV positive and negative children. Older age of the child, previous ear infection, use of TB drugs and long duration on ART among the HIV positive children increase the odds of having hearing loss among children. However, use of NVP was not associated with HL.